IL-22BP controls the progression of liver metastasis in colorectal cancer - Giannou, Anastasios D.; Kempski, Jan; Zhang, Tao; Lücke, Jöran; Shiri, Ahmad Mustafa; Zazara, Dimitra E.; Belios, Ioannis; Machicote, Andres; Seeger, Philipp; Agalioti, Theodora; Tintelnot, Joseph; Sagebiel, Adrian; et al. (Frontiers in Oncology, 2023)
Background: The immune system plays a pivotal role in cancer progression. Interleukin 22 binding protein (IL-22BP), a natural antagonist of the cytokine interleukin 22 (IL-22) has been shown to control the progression of colorectal cancer (CRC). However, the role of IL-22BP in the process of metastasis formation remains unknown. Methods: We used two different murine in vivo metastasis models using the MC38 and LLC cancer cell lines and studied lung and liver metastasis formation after intracaecal or intrasplenic injection of cancer cells. Furthermore, IL22BP expression was measured in a clinical cohort of CRC patients and correlated with metastatic tumor stages. Results: Our data indicate that low levels of IL-22BP are associated with advanced (metastatic) tumor stages in colorectal cancer. Using two different murine in vivo models we show that IL-22BP indeed controls the progression of liver but not lung metastasis in mice. Conclusions: We here demonstrate a crucial role of IL-22BP in controlling metastasis progression. Thus, IL-22 might represent a future therapeutic target against the progression of metastatic CRC.